2018
DOI: 10.1111/sed.12516
|View full text |Cite
|
Sign up to set email alerts
|

A decline in molluscan carbonate production driven by the loss of vegetated habitats encoded in the Holocene sedimentary record of the Gulf of Trieste

Abstract: Carbonate sediments in non‐vegetated habitats on the north‐east Adriatic shelf are dominated by shells of molluscs. However, the rate of carbonate molluscan production prior to the 20th century eutrophication and overfishing on this and other shelves remains unknown because: (i) monitoring of ecosystems prior to the 20th century was scarce; and (ii) ecosystem history inferred from cores is masked by condensation and mixing. Here, based on geochronological dating of four bivalve species, carbonate production du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 110 publications
1
37
0
Order By: Relevance
“…wave energy) processes can mix sediments (Flessa, Cutler, & Meldahl, ; Kosnik, Hua, Kaufman, & Zawadzki, ; Olszewski, ). This mixing is a key process affecting death assemblage composition, as it blends new inputs from the living community with older buried cohorts (Kidwell, ; Tomašových, Gallmetzer, et al, ; Tomašových & Kidwell, ). For this reason, the amount of time‐averaging should be resolved and, depending on the study aims, constrained.…”
Section: Discussionmentioning
confidence: 99%
“…wave energy) processes can mix sediments (Flessa, Cutler, & Meldahl, ; Kosnik, Hua, Kaufman, & Zawadzki, ; Olszewski, ). This mixing is a key process affecting death assemblage composition, as it blends new inputs from the living community with older buried cohorts (Kidwell, ; Tomašových, Gallmetzer, et al, ; Tomašových & Kidwell, ). For this reason, the amount of time‐averaging should be resolved and, depending on the study aims, constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Boxplots show median ages and 25 th and 75 th percentiles, whiskers denote age minima and maxima. Down-core changes in shell ages at Piran (Gouldia minima, Corbula gibba) and Brijuni (Timoclea ovata) are reported in Tomašových et al (2019) and Schnedl et al (2018).…”
Section: Paleoecological Analysismentioning
confidence: 94%
“…Several paleoecological studies have demonstrated effects of overfishing, eutrophication, hypoxia, and pollution on ecosystem composition in the northern Adriatic over the past few centuries based on historical and sediment core data (Barmawidjaja et al 1995;Sangiorgi and Donders 2004;Ferretti et al 2013;Kowalewski et al 2015;Vidović et al 2016;Gallmetzer et al 2017;Tomašových et al , 2019. However, quantitative analyses of benthic assemblages in sediment cores capturing time intervals preceding the past 500 years are rare, and the major ecological turnovers in the northern Adriatic during the entire Holocene remain poorly explored, especially in the north-eastern part (Fiorini and Vaiani 2001;Scarponi and Kowalewski 2007;Rossi and Vaiani 2008;Lotze et al 2011;Coll and Lotze 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations